IMAN KRISTIANI DI TENGAH KEHIDUPAN POLITIK DAN PERDAMAIAN DUNIA: REFLEKSI TEOLOGIS ATAS GAUDIUM ET SPES 73-78 - Yanto Sandy Tjang; Florensius Sutami; Gregorius Kukuh Nugroho; Alexander Maruli Tua Sinaga; Janti Sudono; Kristina Meni; Roida Sihombing; Theresia Lina Iswaraningsih (IN VERITATE LUX, 2026)
The study offers a theological examination of the relationship between Christian faith, political life, and the vocation to build world peace, grounded in Gaudium et Spes articles 73–78. Within the contemporary global context marked by armed conflicts, democratic crises, ideological polarization, and structural injustice, the study reaffirms the enduring relevance of the Second Vatican Council’s social theology for the presence of Christian faith in the public sphere. Employing a qualitative research design, the study is based on a literature review with a textual–contextual analysis of conciliar documents, combined with critical engagement with works in social theology and Christian political ethics. The findings indicate that, from the perspective of faith, politics is understood as a form of service to the common good (bonum commune) and as a concrete arena for the enactment of the ethical responsibility of believers. The relationship between Church and state is articulated through the principle of a healthy and dialogical autonomy, which enables the Church to exercise its moral and prophetic role without succumbing to the logic of power or domination. Furthermore, Gaudium et Spes affirms that authentic peace is not merely the absence of conflict but the fruit of justice rooted in God’s reconciling work in Christ. Accordingly, Christian faith is presented as a transformative force with an essential public dimension, one that fosters the ethical engagement of believers in the pursuit of justice and peace in the world.